Psychological, social, and human capital and career empowerment among women entrepreneurs: A meta-analytic structural equation modeling approach - Juan, Wang; Ayob, Abu Hanifah; Cui, Dingchen (Edelweiss Applied Science and Technology, 2026)
This study integrates fragmented evidence to examine how psychological, social, and human capital jointly influence career empowerment among women entrepreneurs, with work engagement as a mediator and the level of economic development as a key contingency. A meta-analytic structural equation modelling (MASEM) approach was employed to synthesise 49 quantitative studies (N = 31,247 women entrepreneurs, 2015–2025) identified through Web of Science and Scopus using PRISMA 2020 guidelines. Psychological, social, and human capital each exert significant direct and indirect effects on career empowerment through work engagement (partial mediation). Psychological capital shows the strongest total effect, with over half mediated by engagement. The entire process is significantly stronger in developing economies (pooled β = 0.276) than in developed economies (pooled β = 0.184). Work engagement serves as a core motivational mechanism converting capital into empowerment, but its strength is highly context-dependent, with markedly greater impact under institutional constraints. Policymakers and incubators in emerging markets, especially China, should prioritise scalable psychological capital training and engagement-enhancing peer networks to maximise women’s entrepreneurial empowerment.